P-y-ẏ curves for dynamic analysis of offshore wind turbine monopile foundations. Issue 90 (November 2016) - Bayat, M.; Andersen, L.V.; Ibsen, L.B.
Abstract: The well-known p - y curve method provides soil-structure interaction that is independent of the load rate. In this paper an improved p - y curve method is proposed by considering the influence of the excitation frequency. For this purpose, a two-dimensional finite-element program is developed for analysis of a segment of an offshore monopile foundation placed in different depths. The intended use of the model is analyzes of offshore wind turbines in operation where small-magnitude cyclic response is observed in addition to the quasi-static response from the mean wind force. The response to small-magnitude cyclic loading is analyzed by employing coupled equations based on the u - P formulation, i.e. accounting for soil deformation as well as pore pressure. Thus, the paper has focus on the effects of drained versus undrained behavior of the soil and the impact of this behavior on the stiffness and damping related to soil-structure interaction at different load frequencies. In order to enable a parameter study with variation of the soil properties, the constitutive model is purposely kept simple. Hence, a linear poroelastic material model with few material parameters is utilized. Based on the two-dimensional model, linear p - y - y ̇ curves are extracted for the lateral loading of monopiles subjected to cyclic loads. The developed code is verified with findings in the literature. Highlights: A two-dimensional analysis of a monopile segment moving horizontally through saturated soil is analyzed. A p − y − ẏ curve accounting for the rate of pile motion is proposed as an alternative to static p − y curves. The stiffness and damping properties related to soil structure interaction are determined by implementing the u-p formulation for the porous media.